Compounds Isolated from Wikstroemia taiwanensis Regulate Bone Remodeling by Modulating Osteoblast and Osteoclast Activities - Imtiyaz, Zuha; Lin, Yi-Tzu; Liang, Fang-Yu; Chiou, Wen-Fei; Lee, Mei-Hsien (Frontiers in Pharmacology, 2021)
Bone remodeling, a dynamic process in which bone formation by osteoblast is preceded by bone resorption by osteoclast, is a vital physiological process for maintaining bone mass and strength, imbalances in which could precipitate osteoporosis. Due to the unilateral mechanism of the existing bone remodeling drugs, identifying compounds that could regulate the balance between osteoclast and osteoblast could improve the treatment of osteoporosis. Here, we show that compounds isolated from Wikstroemia taiwanensis modulate osteoclast and osteoblast activities. Specifically, astragalin (1) and kaempferol 3-O-β-D-apiofuranosyl-(1→6)-β-D-glucopyranoside (2), besides increasing mineral deposition, increased alkaline phosphatase activity (137.2% for 1 and 115.8% for 2) and ESR-α expression (112.8% for 1 and 122.5% for 2) in primary human osteoblasts. In contrast, compounds 1, 2, 3, and 5 inhibited tartrate-resistant acid phosphatase (TRAP) activity in receptor activator of nuclear factor-κB ligand-induced osteoclasts by 40.8%, 17.1%, 25.9%, and 14.5% and also decreased the number of TRAP-positive cells by 51.6%, 26.8%, 20.5%, and 18.6%, respectively. Our findings, therefore, showed that compounds isolated from W. taiwanensis could increase osteoblast activity while simultaneously decreasing osteoclast activity, and hence, warrant further evaluation for development as anti-osteoporosis agents.